Pharmacophore Modelling as a Virtual Screening Tool for the Discovery of Small Molecule Protein-protein Interaction Inhibitors - Voet, Arnout; Y.J. Zhang, Kam (Current Pharmaceutical Design, 2012)
Pharmacophore searches have become a popular tool for virtual screening of libraries to identify novel active substances that can be potentially developed into drugs. While they have been applied for years on common drug targets, their application in the discovery of protein-protein interaction inhibitors remains limited. This review describes current pharmacophore modelling methods applied in the discovery of novel inhibitors targeting protein-protein interactions. We first address the mimicry of protein-protein interactions with their respective inhibitors as observed in crystal structure complexes. This mimicry can be exploited to derive a pharmacophore query from protein-protein complex structures. We then discuss several cases where pharmacophore queries were utilized for the discovery of first-in-class inhibitors of their respective protein-protein interaction targets. These examples have demonstrated the usefulness of pharmacophore modelling in the quest for protein-protein interaction inhibitors.
Keywords: PUMA